Effects of self-paced high-intensity interval training and moderate-intensity continuous training on the physical performance and psychophysiological responses in recreationally active young adults - Soylu, Yusuf; Arslan, Ersan; Sogut, Mustafa; Kilit, Bulent; Clemente, Filipe (Biology of Sport, 2021)
This study aimed to compare the effects of 8-week self-paced high-intensity interval training (HIIT) vs. self-paced moderate-intensity continuous training (MICT) on the physical performance and psychophysiological responses of young adults. Twenty-eight recreationally active young adults (age: 21.1 ± 1.6 years) were randomly assigned to either the self-paced HIIT (n = 14) or the MICT (n = 14) group training protocol. The HIIT consisted of two 12–24 x 30 seconds of high-intensity runs interspersed by 30 seconds of recovery. The MICT completed 24–48 minutes of continuous running. Before and after the 8-week interventions the following tests were completed: maximum oxygen consumption (V̇ O2max) estimated from the Yo-Yo Intermittent Recovery Test level 1 (YYIRTL-1), repeated sprint ability (RSA), 10–30-m sprint test, change of direction test (T-drill), countermovement jump (CMJ) and squat jump (SJ), and triple hop distance test (THD). Training rating of perceived exertion (RPE) and physical activity enjoyment scale (PACES) were assessed during the training programme. The HIIT resulted in greater improvement in YYIRTL-1, V̇ O2max, RSA and T-drill performances compared to the MICT. Furthermore, RPE and PACES values were higher in the HIIT than the MICT. This study suggested that self-paced HIIT may be a more effective training regime to improve aerobic fitness with greater physical enjoyment in recreationally active young adults.